Obtaining and Characterization of the PLA/Chitosan Foams with Antimicrobial Properties Achieved by the Emulsification Combined with the Dissolution of Chitosan by CO(2) Saturation - Mania, Szymon (Molecules, 2019)
A new method of obtaining functional foam material has been proposed. The materials were created by mixing the poly lactic acid (PLA) solution in chloroform, chitosan (CS) dissolved in water saturated with CO(2) and polyethylene glycol (PEG), and freeze-dried for removal of the solvents. The composite foams were characterized for their structural (SEM, FT-IR, density, porosity), thermal (DSC), functional (hardness, elasticity, swelling capacity, solubility), and biological (antimicrobial and cytotoxic) properties. Chitosan in the composites was a component for obtaining their foamed form with 7.4 to 22.7 times lower density compared to the neat PLA and high porosity also confirmed by the SEM. The foams had a hardness in the range of 70–440 kPa. The FT-IR analysis confirmed no new chemical bonds between the sponge ingredients. Other results showed low sorption capacity (2.5–7.2 g/g) and solubility of materials (less than 0.2%). The obtained foams had the lower T(g) value and improved ability of crystallization compared to neat PLA. The addition of chitosan provides the bacteriostatic and bactericidal properties against Escherichia coli and Staphylococcus aureus. Biocompatibility studies have shown that the materials obtained are not cytotoxic to the L929 cell line.